A cell-penetrating bispecific antibody suppresses hepatitis B virus replication and secretion - Chongwei Xie; Bing Zhou; Da Yao; Xin Wang; Lihong Zhong; Chuanghua Qiu; Junfang Zhang (Virus Research)
Hepatitis B virus (HBV) represents one of the major pathogenic factor that leads to chronic liver diseases and the development of hepatocellular carcinoma (HCC). The currently approved anti-HBV drugs cannot eradicate the virus or block the development of HCC. HBV nucleocapsid consists of the hepatitis B core antigen (HBcAg) and the HBV relaxed-circular partially double-stranded DNA (rcDNA), indispensable in virus replication. The present study reported a cell-penetrating bispecific antibody targeting HBcAg and preS1, fused with the cell-penetrating peptide R9TAT, named Anti-preS1 × Anti-HBcAg-R9TAT. The antibody could recognize preS1 and HBcAg and internalize into living cells efficiently, suppressing the extracellular hepatitis B surface antigen (HBsAg) and hepatitis B envelope antigen, and the intracellular HBsAg and HBcAg in vitro. This cell-penetrating bispecific antibody is a novel approach to suppressing HBV replication and secretion and is a promising anti-HBV therapeutic antibody candidate.